Daily evapotranspiration estimation using limited meteorological data across diverse geographic regions of China - Chen, Wenxu; Wang, Fei; Yuwen, Xingcan; Shi, Yi; Zhao, Xinbo (International Journal of Agricultural and Biological Engineering, 2026)
Evapotranspiration (ET) is a key component of the water cycle, and accurate estimation of reference crop evapotranspiration (ETo) is essential for irrigation management. To build a precise, lightweight ETo estimation model, this study takes key meteorological factors as inputs and applies machine learning models and hybrid models Crested Porcupine Optimizer kernel extreme learning machine (CPO-KELM), the Dung Beetle Optimizer Algorithm KELM (DBO-KELM), and Particle Swarm Optimization KELM (PSO-KELM) to estimate ETo at 38 meteorological stations across China’s seven major geographical regions. The results indicate that maximum temperature (Tmax), average temperature (Tave), and relative humidity (RH) are the primary factors affecting ETo and were therefore used as model inputs. The standalone kernel extreme learning machine (KELM) model shows acceptable ETo estimation performance, with R2, RMSE, MAE, and NSE ranging from 0.802-0.885, 0.512-0.911, 0.464-0.970, and 0.802-0.885, respectively. Hybrid models outperform the standalone KELM, among which CPO-KELM is the most accurate: its R2, RMSE, MAE, and NSE range from 0.881-0.942, 0.413-1.147, 0.284-0.763, and 0.881-0.942. At the regional scale, the CPO-KELM model exhibits its best performance in the Northeast and North China regions, with R2, RMSE, MAE, and NSE ranging from 0.923-0.936, 0.413-0.511, 0.284-0.358, and 0.923-0.936, respectively. In contrast, its weakest performance is observed in parts of South China and Northwest China, with R2, RMSE, MAE, and NSE ranging from 0.881-0.905, 0.675-1.147, 0.506-0.763, and 0.881-0.905. Compared to standalone KELM, CPO-KELM improves accuracy significantly: R2 and NSE rise by 6.4%-9.9%, while MAE drops by 21.3%-38.8%. Thus, the hybrid CPO-KELM model effectively enhances ETo estimation accuracy across China’s regions. Therefore, the proposed CPO-KELM hybrid model provides a high-accuracy and lightweight alternative for ETo estimation in data-scarce regions, and offers reliable technical support for intelligent water resources management and irrigation optimization across diverse climatic zones in China. Keywords: ETo, seven major geographical regions, machine learning algorithm, lightweight model DOI: 10.25165/j.ijabe.20261901.10161 Citation: Chen W X, Wang F, Yuwen X C, Shi Y, Zhao X B. Daily evapotranspiration estimation using limited meteorological data across diverse geographic regions of China. Int J Agric & Biol Eng, 2026; 19(1): 241–250.